Reconstruction of the 236U input function for the Northeast Atlantic Ocean: implications for 129I/236U and 236U/238U-based tracer ages - Christl, Marcus; Casacuberta, Núria; Vockenhuber, Christof; Elsässer, Christoph; Bois, Pascal Bailly du; Herrmann, Jürgen; Synal, Hans-Arno (Journal of geophysical research. Oceans, 2015)
A reconstruction of historical discharges of 236U into the Northeast Atlantic Ocean by nuclear installations is presented. The nuclear reprocessing facilities Sellafield (SF), Great Britain (GB) and La Hague (LH), France and potentially also the nuclear fuel processing installation Springfields (SP), GB represent the main contributors of 236U in the Northeast Atlantic Ocean. Because data on 236U releases is lacking, 236U discharges from SP and SF are estimated based on the U-isotopic systematics found in the discharges from LH. The resulting reconstruction of 236U releases indicates that, until 2013, a total of (95 ± 32) kg of 236U was discharged from SF, SP, and LH. In a second step, the reconstructed 236U releases are combined with 129I data from literature and oceanic and atmospheric box models are used to derive the 129I/236U and 236U/238U input functions that, for example, can be used to calculate tracer ages of Atlantic Waters in the Arctic Ocean. Our conceptual results show that the combination of 129I/236U and 236U/238U generally allows the estimation of tracer ages over the past approximately 25 years if contributions of 236U from global fallout are considered. Finally, as a proof of concept, the new method is applied to calculate tracer ages of Arctic Ocean surface samples (collected in 2011/2012) and the results are in good agreement with literature data. We conclude that the combination of 129I/236U with 236U/238U in a dual tracer approach provides a sensitive tool for the calculation of tracer ages and ventilation rates in the North Atlantic region.